Land Conversion: Transforming Urban Military Baselands To Higher Economic Uses - Mundo, Proscoro Ervin A. (Journal in Urban and Regional Planning; Vol 1 No 1 (2014): Journal in Urban and Regional Planning, 2014)
The defense of the nation’s sovereignty, the protection of the environment and natural resources can be carried out only to the extent that the Philippines can get other nations to respect its rights over its maritime territory, partly through diplomacy and the show of military force. Given the Philippines’ current fiscal situation, there can be little argument that the Armed Forces of the Philippines (AFP) would not be able to pursue its overdue equipment-intensive modernization from traditional sources of government funds. If ever, the level of direct government funding will meet only a fraction of its capability needs. This economic reality calls for creative options: what the AFP lacks in financial assets, it can make up by converting AFP military camps located in various urban areas of the country as equity thru Private-Public-Partnership (PPP) economic activities to generate funds for the currently underfunded AFP modernization program. This novel “project” once “implemented” is expected to generate valuable resources for the DND and the AFP other than the normal cash flow from the annual General Appropriations as stated in the National Expenditure Program. In addition, the project can help directly sustain the country’s inclusive economic growth not counting its attendant local economic activities such the collection of taxes, the creation of thousands of jobs, and most especially the long-term effects of the project to the forward and backward economic linkages of the country, including its direct impact in the generation of wealth for the improvement of the country’s quality of life. Keywords: Public-Private-Partnership, long term lease, military camps, land conversion, generation of wealth, economic linkages, inclusive economic growth